The teaching of cell respiration biochemistry facilitated by a mobile device application (Research, Society and Development, 2022)
Information and Communication Technologies - ICTs, bring new possibilities for teaching and learning topics specific to Biochemistry. Hybrid teaching and active methodologies, associated with educational technological tools, can determine the breaking of paradigms in the scope of pedagogical practice. To analyze the relationship between hybrid teaching and the active inverted classroom methodology, this work used the Bio Respiration application, a teaching tool to facilitate the teaching of cellular respiration. The use of specific questionnaires on the teaching of cellular respiration from the use of the mentioned tool and the analysis of them, characterized its quantitative and qualitative aspects. Students and teachers from the public network of the metropolitan region of Fortaleza / Ce, constituted the sample group. The results obtained demonstrated that the tested tool can assist teachers and students in teaching and learning cellular respiration.